THE MESOZOIC EXTENDED SPONGES - COLONIES WITHIN THE METAMORPHIC PLATTENKALK GROUP OF THE EXTERNAL HELLENIDES - Μανούτσογλου, Ε. (Bulletin of the Geological Society of Greece, 2018)
In the present work the spatiotemporal distribution of relics from extended colonies of sponges that were located and preserved within metamorphic rocks of the Plattenkalk Group of the External Hellenides is presented and discussed. Based on reports regarding extensive occurence of sponges during Upper Jurassic in Europe, published and new data for the occurence of probable Demospongiae in mainly mountainous regions of Southern Péloponnèse and Crete are compiled. This data allow a better palaeoecological approach and a probable partial revision of the evolution of the palaeogeographical deposition area of an important part of the External Hellenides.